The art of dissent from the rhetoric of silence: the terror and promise of Dao and Khora - Goh, Hui Peng Constance (2008)
This thesis reworks the idea of Chineseness as a translational point in its exploration of the intricate knot of nothingness, a sublimity which makes Chinese culture irreducible to the postcolonial, postmodern or poststructuralist movements because what the West arrogates from Eastern philosophy or contrariwise is simultaneously an interrogative advancement and a detour to selfsameness. Derrida's deconstructive absence in Chinese writing may be surprising to those acquainted with his eloquence on phonetic writing and the Egyptian hieroglyphs. By (dis)locating the commentaries revolving around Derrida's reticence on Chinese inscriptions, I shall launch the argument from what most have put down merely as a "lack" of knowledge, inverted here to expose the always already missing link between the articulator and reality. Derrida's cryptic remark about Chinese writing as "the testimony of a powerful movement of civilization developing outside of all logocentrism" can be read as a suggestion of a certain parallelism between deconstruction and Eastern philosophy, accidentally encountering in this paper. The signifying dissemination within writing is most advantageous to the reading of dao and khora as synonymous sites and only meeting with a supplementary inversion, an ironic twist, at the divide between the East and the West. This Lacanian knot, a result of the encore of centres, is reconciled provisionally with a deus ex machina, the "parallax view" of Slavoj Zizek, the interpretative (l)ink. As part of the many chiasmic encounters, it is the assertion here that Derrida's rewriting of the Heideggerean Dasein, "There is nothing outside the text", signals the revolutionary aestheticisation of the ontological contours which gives to a replete subjectivity, political or otherwise. Inversely, the ontological disclosure in and through aesthetics provides impetus to epistemology. And the circular relations between aesthetics and existential ethics are that which provides the possibility of reconciliation with alterity, the trace that inevitably keeps reading open. Given that we can relate the ethical only to the contextual, the contingency underlying its very definition discloses an indeterminacy that ensures openness to the future, and, coupled with the readiness to respond to the call of the other, prompts a re-reading as reading irresponsibly. In other words, the semiotic coming-to-be reciprocates the coming-to-be of the human entity. Derrida's silence about Chinese writing may be a gesture to the signifying reticence at the heart of discourse, simultaneously the poetic place and moment, which enables this critical traversal, a wayfaring entailing the bearing of the past so that alterity can be imag(in)ed, the "supernumerary" of both dao and khora, with the disablement of a fixed discursive trajectory.